2019
DOI: 10.1007/s00779-019-01206-3
|View full text |Cite
|
Sign up to set email alerts
|

Personal pollution monitoring: mobile real-time air quality in daily life

Abstract: Poor air quality is a growing global health concern that impacts millions of people worldwide. Although we are beginning to understand the health impacts of air pollution, it remains a challenge to provide people with the information they need to be able to make health-conscious choices. The CitiSense system gives individuals the realtime tools they need to be able to identify when and where they are exposed to poor air. We present the results of a qualitative study regarding a 4-week "in the wild" deployment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…These stations provide accurate measurements, generally on an hourly basis, for their exact location but as hourly mean levels of pollutants vary considerably over tens of metres, this level of coverage cannot provide accurate exposure data for citizens [12][13][14][15]. The rapid variation in urban pollution levels is due to the strong influence of local sources and meteorological conditions, as well as street canyon effects in these areas [16]. The traditional monitoring strategy does not account for indoor exposure which can be greatly elevated relative to outdoor, for instance through use of solid-fuels for heating and cooking, emissions from the cooking itself, and household aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…These stations provide accurate measurements, generally on an hourly basis, for their exact location but as hourly mean levels of pollutants vary considerably over tens of metres, this level of coverage cannot provide accurate exposure data for citizens [12][13][14][15]. The rapid variation in urban pollution levels is due to the strong influence of local sources and meteorological conditions, as well as street canyon effects in these areas [16]. The traditional monitoring strategy does not account for indoor exposure which can be greatly elevated relative to outdoor, for instance through use of solid-fuels for heating and cooking, emissions from the cooking itself, and household aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Hence numerous works propose systems to monitor and predict ambient air pollution. Studies in [17], [18], [19] demonstrate various solutions for outdoor air quality, while other papers such as [20], [21], [22] and [23] consider both environment types.…”
Section: A Environment Typementioning
confidence: 99%
“…Crowd-sensing is another widespread approach to monitor air pollution. For example, authors in [21], [32] and [33] collect data from participants, whereas [22] collects data from both, sensors and crowd. Open-source data, national weather and pollution monitoring centers and internet-connected monitoring stations are other forms of data sources in the literature [17], [23], [30], [34].…”
Section: E Data Acquisitionmentioning
confidence: 99%
“…The few studies that do exist are insightful, providing preliminary conclusions to suggest that personal exposure information can challenge preconceptions and inform people's responses to air pollution. In relation to perceptions and emotions, the reported effects of monitor use range from an increased awareness of air pollution and intense emotional reaction (Oltra et al 2017), through to enjoyment and surprise (Bales et al 2019;Wong-Parodi et al 2018;Bales et al 2012). In relation to behaviour, Wong-Parodi et al (2018) and Zappi et al (2012) found minor behaviour changes to occur, which include actions like closing windows and ceasing to burn incense indoors, while Oltra et al (2017) did not witness any alteration-intentional or real-as a result of monitor use.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a one-dimensional account of how monitors may affect behaviour. Finally, there are a myriad of shared shortcomings pertaining to the methodologies deployed; the majority of existing studies draw on relatively small and homogenous samples, while Zappi et al (2012) and Bales et al (2019;2012) use figures from the same study conducted almost a decade ago, although the latest iteration is augmented with more recent data.…”
Section: Introductionmentioning
confidence: 99%